Akaoraora’ia te peu ‘ā to ‘ui tūpuna: Culturally Responsive Pedagogy for Cook Islands Secondary School Physical Education - Te Ava, Aue; Rubie-Davies, Christine; Airini; Ovens, Alan (The Australian Journal of Indigenous Education, 2013)
This research examines outcomes from introducing cultural values into Cook Islands secondary schools during two cycles of action research comprising planning, implementing, observing and reflecting. The cultural values upon which the physical education lessons were based were: tāueue (participation), angaanga kapiti (cooperation), akatano (discipline), angaanga taokotai (community involvement), te reo Maori Kuki Airani (Cook Islands Maori language), and auora (physical and spiritual wellbeing). The cultural values were believed to be an essential element of teaching physical education but one challenge was how to assist teachers to implement the cultural values into classroom teaching as most participant teachers were not Cook Islanders. Findings from this action research project suggest that while participant teachers and community cultural experts may agree to incorporate cultural values in teaching Cook Islands secondary school students, teachers nonetheless find difficulties in implementing this objective.